Epidemiology of paragonimiasis in Colombia (2022)
eng: Five newly discovered endemic foci for paragonimiasis in Colombia are described for the first time. The disease was diagnosed in 24 people from the Embera Indian communities located at the Colombian Pacific Coast and investigated in 1993–1998. We also describe the clinical, epidemiological and treatment response aspects. In these foci an Aroapyrgus sp. snail different from A. colombiensis was found to be the first intermediate host, and the crab Hypolobocera emberarum nsp. the second intermediate host.